БЎЛАЖАК ЎҚИТУВЧИЛАРНИНГ ПЕДАГОГИК ФАОЛИЯТИДА КАСБИЙ-ПЕДАГОГИК ҲАМКОРЛИККА ТАЙЁРЛАШНИНГ НАЗАРИЙ АСОСЛАРИ - Махамматова, С.С. (SCIENCE and SOCIETY, 2024)
In this article, the psychological scientific analysis of the results are covered of the socio-psychological questionnaire to determine the factors and mechanisms of students' interest, ability, inclination to the profession and their application in practice
Keywords: activity; cooperation; education; method; capabilities; inclinations